Amylin: pancreatic hormone of glucose regulation - Gonçalves, Ana Maria (1998)
Type I or late-stage (insulin-deflcient) type II diabetes is characterized by impaired glucose homeostasis that results from the destruction of pancreatic {>cells and subsequent loss of insulin production. ln many patients optimal metabolic control, essential for the prevention of diabetic complications, is diflcult to obtain. Abnormalities of gastric emptying are now recognized contributors to variations in glycemic control. Amylin is now recognised as the third pancreatic hormone involved in the control of glucose homeostasis. lts actions include the modulation of gastric emptying while diverse other effects are still under discussion. Today, recognition of the fact that the level of this hormone is diminished in diabetic patients, together with know ledge of its actions, leads to a possible new future therapeutic perspective involving the admi nistration of amylin analogues.